APB UiTM Perlis highlights politeness strategies for better communication - Chulan, Majdah; Nayan, Surina; Razali, Razlina (Institut Kualiti dan Pengembangan Ilmu (InQKA), 2024)
18 October 2024, Arau – The Academy of Language Studies (APB) UiTM Cawangan Perlis successfully organised a webinar on Politeness Strategies in Communication last Friday. 96 participants which included students and staff of UiTM Perlis and others joined the online program. Among the objectives of the webinar was to provide a platform for students and others to have dialogues and exchange their ideas and opinions to facilitate their learning and also impart knowledge on politeness strategies in everyday communication.